The Influence of Reward, Punishment and Motivation on Employee Performance at PT Budi Kurnia Sejahtera - Aries Sundoro (Socio-Economic and Humanistic Aspects for Township and Industry, 2023)
In recent years, company management has revealed that human resources have the most significant and important role in obtaining competitive advantage and sustainable efficiency. This research aims to examine the influence of reward, punishment and motivation on employee performance. Employee performance is a research topic that still needs to be carried out, because human resources are one of the important factors in the running of a company's operational activities. This research uses a sample of PT. Budi Kurnia Sejahtera employees using hair theory calculations. The data analysis method used is multiple linear regression analysis with the help of the SPSS version 25 program. Research shows that reward, punishment and motivation have a positive and significant influence on employee performance. The positive influence of all aspects of research means that management needs to improve factors that can improve its performance so that the company's sustainability is maintained.